Pelatihan e-SPT untuk meningkatkan Keterlibatan Mahasiswa dalam Mendorong Kepatuhan Pajak - Sahad Sakhdiyah, Sahad Sakhdiyah; Mohammad Ryan Badruzzaman, Mohammad Ryan Badruzzaman; Mohammad Firdaus Al-Fattar, Mohammad Firdaus Al-Fattar; Dodi Setiawan, Dodi Setiawan; Natalina, Sri Anugrah; Utama, Yopi Yudha; Zunaidi, Arif; Kusumawardhani, Sayekti Indah; Muyasaroh, Isyrohil; Ardika, Rendi; Aditya, Tony; Yuliani, Yuliani; Rahardi, Deto (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The aim of this service is to increase the understanding and skills of the community, especially small and medium enterprises (UKM), in using the e-SPT application to report their tax obligations. The service method used is the presentation method, where sharia accounting students from IAIN Kediri present material systematically through PowerPoint slides and live demonstrations. The results of the service showed the participants' active participation in practical and discussion sessions, which deepened their understanding of the use of e-SPT. Post-activity evaluation showed a high level of satisfaction from participants with the material and method of delivering the training. This activity succeeded in providing real benefits by increasing tax compliance and the use of tax technology among the community, as well as strengthening students' commitment to making positive contributions to society through the dedication of their knowledge and skills.